The Effect of Applying the Random Text Strategy on Teaching Reading Skills among Seventh-Grade Students at Nur Al-Iman Al-Barakah Islamic Junior High School Tangerang - Rifa Nurul Syafiqoh; Iman Matin; Achmad Fudhaili (Penerbit Minhaj Pustaka, 2026)
This study aims to determine the effect of applying the Random Text Strategy in developing Arabic reading skills among seventh-grade students at MTs Nurul Iman Al-Barkah Tangerang. The background of this research lies in the low reading ability of students due to the use of traditional teaching methods that are teacher-centered and do not actively involve students in the learning process, which results in low learning motivation and difficulties in understanding Arabic texts accurately. This research employed a Mixed Method approach with a One Group Pretest–Posttest experimental design. The sample consisted of all seventh-grade students, totaling 20 participants. Data were collected through observation, interviews, and written tests (pretest and posttest). Quantitative analysis used the t-test and Cohen’s d to determine the effect size, while qualitative data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the average posttest score of 80.15 was higher than the average pretest score of 60.8. The obtained t value (t₀ = 16.39) exceeded the t table value at the 5% and 1% significance levels, indicating that the alternative hypothesis (H₁) was accepted while the null hypothesis (H₀) was rejected. The Cohen’s d value of 3.66 also indicated a highly significant effect of the Random Text Strategy on improving the students’ reading skills. Thus, it can be concluded that the Random Text Strategy is highly effective and significant in enhancing Arabic reading skills. It also contributes to increasing students’ learning motivation, active participation, critical thinking skills, and deeper comprehension of Arabic texts.